2018
DOI: 10.1007/s10967-018-6343-x
|View full text |Cite
|
Sign up to set email alerts
|

Radioactivity of honey from northern Poland

Abstract: This work shows significant variations in the values of 210 Po in different analyzed Polish voivodeships. Statistical analysis of 210 Po activity concentrations in honey samples showed significant differences between place of honey collecting, kind of honey and morphological structure of plants from which bees collected nectar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The results of the research indicated an increased content of polonium in certain areas that are associated with the development of many branches of industry (e.g., the chemical industry, the petrochemical and sodium industries, as well as the fertilizer industry). Finally, the authors concluded that honey consumption is safe and has no negative impact on human health [61]. Pipoyan et al [62] indicated that Cu concentrations were above the maximum allowed level in several types of honey from Syunik, a region in Armenia owned by the mining industry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the research indicated an increased content of polonium in certain areas that are associated with the development of many branches of industry (e.g., the chemical industry, the petrochemical and sodium industries, as well as the fertilizer industry). Finally, the authors concluded that honey consumption is safe and has no negative impact on human health [61]. Pipoyan et al [62] indicated that Cu concentrations were above the maximum allowed level in several types of honey from Syunik, a region in Armenia owned by the mining industry.…”
Section: Discussionmentioning
confidence: 99%
“…Amounts of heavy metals (Pb, Cd, and Zn) above the permissible limit contained in honey samples collected in the mentioned area were determined [60]. Boryło et al (2019) examined the radioactivity of honey from northern Poland. The results of the research indicated an increased content of polonium in certain areas that are associated with the development of many branches of industry (e.g., the chemical industry, the petrochemical and sodium industries, as well as the fertilizer industry).…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of the effective dose due to water and food consumption in the world population varies according to geographic specificity, seasonal cultural and food habits, in the range 0.2-0.8 mSv year −1 [1]. There are many studies to assess the annual effective dose due to ingestion of radionuclides by food consumption [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], and by water consumption , which use different calculation methods of this physical magnitude.…”
Section: Introductionmentioning
confidence: 99%